Peran Sistem Data Base Dan Security Pada PT. Aplikasi Karya Anak Bangsa (Gojek Indonesia) - Edy Susanto; Alvionita Dairo Lende; Akmal Riza Firjatullah; Reza Almasyah Pratama (Universitas 45 Surabaya, 2023)
Information is one of the company's most important assets. With the rapid development of information technology, the possibility of information security disturbances is increasing. For this reason, the company PT Gojek Indonesia must implement the right policy to protect its information assets. Indirectly, information security is one of the concerns of companies and customers. Therefore, it is necessary to have standardization implemented in the company as a guide in maintaining important assets such as data and information that are considered sensitive to the company. The method used is a qualitative method by studying and observing the existing securities at PT Gojek Indonesia. Gojek strives to maintain the information security of its users by using many advanced and updated systems to avoid the risks they get.